ОБЕСПЕЧЕНИЕ КАЧЕСТВА ПРОФЕССИОНАЛЬНОГО ОБРАЗОВАНИЯ В СООТВЕТСТВИИ С УРОВНЯМИ МЕЖДУНАРОДНОЙ СТАНДАРТНОЙ КЛАССИФИКАЦИИ ОБРАЗОВАНИЯ - Курбанов, Х. (SCIENCE and SOCIETY, 2022)
The article discusses the classification of national educational programs in accordance with the International Standard Classification of Education (here in after – ISCED), which are the main tool for systematization of information on the education system, educational programs and relevant qualifications used to compare data on ISCE levels and assistance in their interpretation at the international level.